Analysis of Audience Reception on Process Message Through Preaching - Ronny Simorangkir (Publikasi Indonesia, 2022)
The Covid-19 pandemic that occurred in the midst of the era of information technology development made the dissemination of information occur significantly everywhere, one of which was messages about prokes through sermons. This study used qualitative research methods, while the data collection techniques were carried out by interviews, observations and documentation. The results of the study show that the Prokes message from the Preacher and Congregation during the Covid-19 pandemic, it turns out that almost all messages conveyed by the communicator are not conveyed and are actually interpreted differently by the communicant, in this case the congregation. Distortion of the meaning of the message received by the communicant is due to the way of delivery and the delivery limit space using the media which is often disturbed and the differences in the characteristics and background of the communicant who have not fully understood the use of electronics fluently, so that there is often ambiguity in the meaning of the message.